On the research concerning the relations between logistics and strategic management – towards the strategic logistics concept in management - Matwiejczuk, Rafał (Z badań nad relacjami między logistyką a zarządzaniem strategicznym. W kierunku strategicznej koncepcji logistyki w zarządzaniu, 2019)
Logistics occupies an important place within two contemporary, influential streams of strategic management: (1) market-based strategic management and (2) resource-based strategic management. Logistics also significantly contributes to the development of business models which are based on the strategic logistics concept. The aim of the article is to identify the most significant relations occurring between logistics and strategic management. The article presents the nature of the logistics concept and its relations with business management, the brief characteristics of market- and resource-based strategic management streams, the most important relations between logistics and these streams, the logistics strategy and its place and role in strategic management, and finally the premises of the strategic logistics concept development as well as the role of the logistics concept in business model development. The article is an introduction to in-depth research planned in the nearest future
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 6, s. 171-183
Keywords: logistics; logistics concept; strategic management; logistyka; koncepcja logistyki; zarządzanie strategiczne